An IoT-based Baby Scales for Stunting Monitoring in Indonesia - Sofie, Mohamad; Olla, Patrisius Kusi; Kusumaningtyas, Pramesti; Chambali, Fani Maduratni (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
The Indonesian government has tried to do prevention stunting case by monitoring and recording the toddlers growth. The problems are the process of recording and entering toddler growth data is still done manually. This is not effective if done over a large area such as in Indonesia because it takes a long time to collect data and has a large possibility of recording errors. The aim of this research is to design an IoT-based baby scale by adding Node MCU ESP32 in to digital baby scales; so the data read by the scales recorded directly in the central data base. The scales are connected to the data base and web page via a WiFi network. The measurement data will be processed in the cloud to obtain a nutritional status classification. It makes the process of determining nutritional status faster. Based on the research conducted, the use of IoT-based baby scales can simplify the process of measuring toddlers' weight and height. The results of unit testing show that the tool is running well with the level of accuracy are 0,3% still within tolerance limits. The next research is expected to add location features, resumes per area and improve access levels on web pages for data security.